The pattern of back pain: from spondyloarthritis to lymphoma - Mulyk , Kateryna; Dzhus , Marta; Karasevska Тetyana; Liubarets , Tetyana (The Ukrainian Scientific Medical Youth Journal, 2024)
inflammatory back pain, which rheumatologists often deal with in their practice, has certain characteristics. However, other non-rheumatological diseases can mimic inflammatory back pain. Non-compliance with the diagnostic criteria and the presence of additional symptoms, especially from the group of "red flags", such as weight loss, fever, night sweats, etc., require careful diagnosis. The purpose of the work is to analyze a clinical case of diffuse large B-cell lymphoma in a young patient with non-specific symptoms, differential diagnosis with seronegative spondyloarthritis associated with inflammatory bowel disease. The article uses the data of objective, instrumental and laboratory examination of the patient. The work presents a clinical case of back pain in a 27-year-old patient, in which a multidisciplinary approach and specific diagnostic procedures (lymph node biopsy, histological and immunohistochemical examination) made it possible to establish the final diagnosis - diffuse large B-cell lymphoma. Based on a clinical case, a review of the literature was performed with an emphasis on the differential diagnosis between rheumatic inflammatory back pain and other causes, including paraneoplastic pain and metastatic processes. The most common causes of chronic back pain in young men are spondyloarthritis, however, in the presence of weight loss, fever, night sweats and lymphadenopathy, back pain requires careful clinical, laboratory and instrumental examination of patients. Diffuse large B-cell lymphoma can be the cause of back pain, which requires the involvement of specialists of various profiles in order to verify the final diagnosis.